EXPLORING UNIVERSITY STUDENTS' PERCEPTIONS OF INDONESIA'S 12% VALUE ADDED TAX INCREASE: THE INFLUENCE OF ECONOMIC LITERACY AND INFORMATION EXPOSURE: Kenaikan ppn 12% - Rifansyah Bayu Pratama; Imahda Khoiri Furqon (Universitas Tulungagung, 2024)
Value Added Tax (VAT) is one of Indonesia's primary sources of government revenue and plays a significant role in supporting fiscal sustainability. The increase in the VAT rate from 11% to 12% has generated diverse public responses, particularly among young adults, yet limited empirical research has examined university students' perceptions of this policy. This study aims to investigate the perceptions of students at K.H. Abdurrahman Wahid State Islamic University Pekalongan regarding the implementation of the 12% VAT increase. A quantitative survey approach was employed using a structured online questionnaire administered to students of the Islamic Economics Study Program through purposive sampling. The collected data were analyzed using descriptive statistical techniques, including frequency distributions and percentage analysis, to identify patterns in students' awareness, perceptions, and responses to the policy. The findings reveal that although most students are aware of the VAT increase, their understanding of its fiscal objectives and economic implications remains limited. Social media serves as the primary source of policy information, while higher education institutions play a relatively minor role in promoting economic literacy. Students also reported varying perceptions regarding the policy's impact on personal expenditures and its fairness, with these differences influenced by socioeconomic conditions and financial circumstances. Furthermore, respondents emphasized the need for more effective government communication and complementary support measures, such as scholarship programs, to mitigate the policy's impact on vulnerable groups. The study contributes to the literature on public perceptions of fiscal policy and provides practical insights for policymakers and educational institutions to enhance economic literacy and improve public acceptance of taxation reforms.